CORRELATION OF AUDITORY, INTELLECTUALLY, REPETITION (AIR) LEARNING MODELS ON STUDENT ACHIEVEMENT - Andina Halimsyah Rambe; Siti Aisyah (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2023)
This study evaluates the correlation between Santri's learning achievement in the Arabic Language Development Institute (LPBA) at PP. Mambaul Ulum Bata-Bata and the auditory, intellectual, and repetition (AIR) learning model. The main objective is to find out how the AIR learning model affects students' learning achievement. This quantitative study used product moment correlation analysis to evaluate the relationship between the AIR learning model and students' learning achievement. There was a strong link between the intellectual, auditory, and repetition parts of the AIR learning model and how well students learned, as shown by an r count of 0.676, which is higher than the critical number (r table) of 0.235. This shows that the AIR learning model has a great impact on students' learning achievement in LPBA at PP. Mambaul Ulum Bata-Bata. This study provides important insights for teachers and policymakers on how to improve the way Islamic schools teach and design their programs.